Healthcare-use for Major Infectious Disease Syndromes in an Informal Settlement in Nairobi, Kenya - Breiman, Robert F; Olack, Beatrice; Shultz, Alvin; Roder, Sanam; Kimani, Kabuiya; Feikin, Daniel R; Burke, Heather (Journal of Health, Population and Nutrition, 2011)
A healthcare-use survey was conducted in the Kibera informal settlement in Nairobi, Kenya, in July 2005 to inform subsequent surveillance in the site for infectious diseases. Sets of standardized questionnaires were administered to 1,542 caretakers and heads of households with one or more child(ren) aged less than five years. The average household-size was 5.1 (range 1-15) persons. Most (90%) resided in a single room with monthly rents of US$ 4.50-7.00. Within the previous two weeks, 49% of children (n=1,378) aged less than five years (under-five children) and 18% of persons (n=1,139) aged ≥5 years experienced febrile, diarrhoeal or respiratory illnesses. The large majority (>75%) of illnesses were associated with healthcareseeking. While licensed clinics were the most-frequently visited settings, kiosks, unlicensed care providers, and traditional healers were also frequently visited. Expense was cited most often (50%) as the reason for not seeking healthcare. Of those who sought healthcare, 34-44% of the first and/or the only visits were made with non-licensed care providers, potentially delaying opportunities for early optimal intervention. The proportions of patients accessing healthcare facilities were higher with diarrhoeal disease and fever (but not for respiratory diseases in under-five children) than those reported from a contemporaneous study conducted in a rural area in Kenya. The findings support community-based rather than facility-based surveillance in this setting to achieve objectives for comprehensive assessment of the burden of disease. Key words: Acute respiratory infection; Diarrhoeal diseases; Febrile illness; Healthcare-seeking; Healthcareuse; Informal settlements; Pneumonia; Slums; Urbanization; Kenya DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7854 J HEALTH POPUL NUTR 2011 Apr;29(2):123-133